Intuitive eating is associated with elevated levels of circulating omega-3-polyunsaturated fatty acid-derived endocannabinoidome mediators. (1st January 2021) - Rochefort, Gabrielle; Provencher, Véronique; Castonguay-Paradis, Sophie; Perron, Julie; Lacroix, Sébastien; Martin, Cyril; Flamand, Nicolas; Di Marzo, Vincenzo; Veilleux, Alain
Abstract: The regulation of food intake and eating behaviours involves interactions between different systems. The endocannabinoidome, comprising several fatty acid-derived mediators, plays a central role in the regulation of food intake. Alterations of this system have been suggested to intervene in the aetiology of eating disorders. This study aimed to examine the associations between non-pathological eating behaviours and circulating endocannabinoidome mediators in a heterogeneous human population. Plasma 2-monoacyl-glycerol and N -acyl-ethanolamine congeners were measured by LC-MS/MS in a sample of 190 men and women. Eating behaviours were assessed using the Three-Factor Eating Questionnaire (TFEQ) and the Intuitive Eating Scale-2 (IES-2). Following adjustment for body mass index and age, plasma levels of omega-3 polyunsaturated fatty acid-derived 2-monoacyl-glycerols, 2-eicosapentaenoyl-glycerol (2-EPG) and 2-docosapentaenoyl-glycerol (2-DPG), were associated with higher intuitive eating scores (0.15 ≤ rho ≤ 0.20; p  < 0.05). These associations were independent of the dietary intake of the fatty acid precursors of these 2-monoacyl-glycerols. However, almost no association was found between plasma levels of N -acyl-ethanolamine congeners and the TFEQ or the IES-2 scores. The results of the present study suggest the association of 2-monoacyl-glycerols, especially 2-EPG and 2-DPG, in the regulation of intuitive eating and the potential implication therein of bioactive lipids.